Sensationalists United? Football hooliganism and the English press. Issue 2 (7th February 2016) - Steen, Rob
Abstract: In the course of researching the Heysel tragedy and its coverage by the media, I pored over dozens of valuable dissections of football hooliganism by renowned sociologists, almost all of whom charged journalists with both exaggerating and exacerbating the problem. Interviews with the accused, unaccountably, were conspicuous by their absence. These scholarly explorations were also accompanied, in my reading, by a widespread tendency to diminish the havoc wrought by criminal and profoundly antisocial behaviour. Many contributory factors were commonly cited, such as 'frustrated maleness', high unemployment, Margaret Thatcher's declaration that 'there is no such thing as society' and the excesses of a small, entirely unrepresentative minority. The prime scapegoats, instead, have been the media – especially the space-starved, time-pressed daily newspapers, as ever, the most inviting of open goals. Their alleged crimes were wilful, irresponsible hyperbole; in short, sensationalism. Written by a sports journalist and journalism lecturer, this paper addresses whether such stereotyping is justified.